Modification of Pacific water in the northern Canadian Arctic - Igor A. Dmitrenko; Sergei A. Kirillov; Bert Rudels; Nicolas-Xavier Geilfus; Nicolas-Xavier Geilfus; Jens Ehn; David G. Babb; David A. Lilien; Dorthe Dahl-Jensen; Dorthe Dahl-Jensen (Frontiers in Marine Science, 2023)
The oceanography of the northern Canadian Arctic Archipelago (CAA) remains poorly studied. Here we present a unique set of conductivity–temperature–depth (CTD) and nitrate profiles collected in a fjord system around Axel Heiberg Island in the northern CAA during April–May 2022. The profiles are examined within the context of upstream observations in the Arctic Ocean and downstream observations in the central CAA, and reveal the origin of water masses and their interactions with ambient water from the continental slope and the nearby tidewater glacier outlet. The subsurface water (~25–180 m depth) is associated with the Pacific water outflow from the Arctic Ocean. The underlying halocline separates Pacific water from a deeper layer of polar water that has interacted with the warm (>0°C) Atlantic water observed below 240 m depth. Pacific water is significantly modified compared to the adjoining Arctic Ocean, as evidenced by the following details. Cold water intrusions from the tidewater glacier create deviations of ~0.25°C in the temperature profile through the subsurface water down to a depth of 140 m. Profiles show no thermal signature of Pacific summer water. Compared to the adjacent Arctic Ocean, the deeper fraction of Pacific-derived water and the Atlantic-modified polar water are warmer, while the underlying Atlantic water is colder. Overall, our results suggest that Pacific and Atlantic water in this area of the northern CAA are modified due to enhanced vertical mixing in a narrow band over the continental slope and shelf off the CAA, and are further modified by interactions with outlet glaciers in the area. This implies that tracing the initial thermohaline signature of the Pacific and Atlantic water flow through the CAA seems to be hardly possible without the use of additional tracers. We also find evidence of geothermal heating near the seafloor, which is not surprising given the observed presence of terrestrial geothermal vents around Axel Heiberg Island, and speculate this heat flux limits ice growth near the glacier terminus.